Water pollutant monitoring by a whole cell array through lens-free detection on CCD. Issue 6 (22nd January 2015) - Tsai, Hsieh-Fu; Tsai, Yi-Ching; Yagur-Kroll, Sharon; Palevsky, Noa; Belkin, Shimshon; Cheng, Ji-Yen
Abstract : This is a portable system for water contamination monitoring. Using live bacterial cells as bioreporters, we integrate temperature control, microfluidic sample introduction, bioluminescence detection, and recording software into a complete system. Abstract : Environmental contamination has become a serious problem to human and environmental health, as exposure to a wide range of possible contaminants continuously increases due to industrial and agricultural activities. Whole cell sensors have been proposed as a powerful tool to detect class-specific toxicants based upon their biological activity and bioavailability. We demonstrated a robust toxicant detection platform based on a bioluminescence whole cell sensor array biochip (LumiChip). LumiChip harbors an integrated temperature control and a 16-member sensor array, as well as a simple but highly efficient luminescence collection setup. On LumiChip, samples were infused in an oxygen-permeable microfluidic flow channel to reach the sensor array. Time-lapse changes in bioluminescence emitted by the array members were measured on a single window-removed linear charge-coupled device (CCD) commonly used in commercial industrial process control or in barcode readers. Removal of the protective window on the linear CCD allowed lens-free direct interfacing of LumiChip to the CCD surface for measurement with high light collection efficiency. Bioluminescence induced by simulated contamination events was detected within 15 to 45 minutes. The portable LumiSense system utilizing the linear CCD in combination with the miniaturized LumiChip is a promising potential platform for on-site environmental monitoring of toxicant contamination.